2013
DOI: 10.3389/fphys.2013.00093
|View full text |Cite
|
Sign up to set email alerts
|

Phenotypic approaches to drought in cassava: review

Abstract: Cassava is an important crop in Africa, Asia, Latin America, and the Caribbean. Cassava can be produced adequately in drought conditions making it the ideal food security crop in marginal environments. Although cassava can tolerate drought stress, it can be genetically improved to enhance productivity in such environments. Drought adaptation studies in over three decades in cassava have identified relevant mechanisms which have been explored in conventional breeding. Drought is a quantitative trait and its mul… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

10
199
1
8

Year Published

2016
2016
2023
2023

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 192 publications
(218 citation statements)
references
References 75 publications
10
199
1
8
Order By: Relevance
“…This observation was contrary to the prediction by Hershey [23] and Okogbenin et al [17] who indicated that productivity in cassava at six MAP can be used as a criterion to screen for high-yielding cassava varieties because early fresh storage root yielders are the higher yielders at later stages of growth. Genotypes that had low storage root yield at 6 months but high yield at 12 MAP might have used the above ground part as the major sink before partitioning materials into storage roots.…”
Section: Pattern Of Storage Root Bulkingcontrasting
confidence: 55%
See 3 more Smart Citations
“…This observation was contrary to the prediction by Hershey [23] and Okogbenin et al [17] who indicated that productivity in cassava at six MAP can be used as a criterion to screen for high-yielding cassava varieties because early fresh storage root yielders are the higher yielders at later stages of growth. Genotypes that had low storage root yield at 6 months but high yield at 12 MAP might have used the above ground part as the major sink before partitioning materials into storage roots.…”
Section: Pattern Of Storage Root Bulkingcontrasting
confidence: 55%
“…Though most crops have specific phases in their phenology that can be targeted for improvement against drought, it has not been easy to do so for cassava due to differential partitioning of dry matter into the above ground biomass and roots [4,7]. High-yielding cassava cultivars have a high bulking rate over a long period of time, whereas cultivars with intermediate and low storage root yield have a low bulking rate of shorter duration or lower bulking rate for longer duration [17,23].…”
Section: Pattern Of Storage Root Bulkingmentioning
confidence: 99%
See 2 more Smart Citations
“…One of the reasons for the high tolerance of cassava during dry periods is its highly sensitive stomatal system. In low moisture soil conditions, the plant saves water by controlling transpiration; however, long periods with severe dry spells during the cycle decrease yield (Oliveira et al 1982, Okogbenin et al 2013. Air temperatures in October and November, during phases of tuber bulking, vegetative growth and the beginning of starch accumulation were the other variables that had a large influence on sweet cassava yield, with a direct relation (+).…”
Section: Resultsmentioning
confidence: 99%